Pelatihan Perawatan Sistem Pendingin Kendaraan Operasional bagi Petugas Penanganan Prasarana dan Sarana Umum - Yongkimandalan, Nicky; Janan, Syifaul; Harlianto, Didi (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
The cooling system is one of the essential components in motor vehicles that requires proper maintenance. Disruption in the performance of the cooling system can lead to an increase in the engine's operating temperature. Ultimately, an overheated engine can cause reduced performance, damage to engine components, and even systemic component failure in motor vehicles. The purpose of this community service activity is to enhance the knowledge of Public Infrastructure and Facilities Handling (PPSU) officers in maintaining the cooling systems of their operational vehicles, which are three-wheeled motorcycles. To achieve this goal, we conducted a workshop at the RW.016 Secretariat, West Cengkareng, West Jakarta. As a result of this activity, PPSU officers in the area have increased their understanding of what needs to be done regularly to ensure the optimal performance of their operational vehicles' cooling systems. An optimally performing cooling system allows the operational vehicles to function properly, ultimately leading to maximum performance by the PPSU officers.